Coordination Chemistry of Polynitriles, Part XI. Influence of 4,4′-Bipyridine and Solvent on the Crystal and Molecular Structures of Alkaline Earth Pentacyanocyclopentadienides - Patrick R. Nimax; Karlheinz Sünkel (Chemistry, 2022)
The reaction of alkaline earth pentacyanocyclopentadienides with 4,4′-bipyridine in MeOH yielded undefined products of composition [M(PCC)2(Bipy)x(MeOH)y(H2O)z] (PCC = [C5(CN)5]−). Recrystallization from MeOH, EtOH, or n-BuOH gave crystals of [Mg(H2O)4(4,4′-bipy)2](PCC)2∙2BuOH (1), [Ca(H2O)4(4,4′-bipy)2](PCC)2∙(4,4′-bipy) (2), [Sr(MeOH)8](PCC)2∙3(4,4′-bipy) (3), [Sr2(H2O)4(BuOH)4(PCC)2(µ-PCC)2 (µ-4,4′-bipy)]∙4 (4,4′-bipy)∙0.29 (BuOH) (4), [Ba3(H2O)4(EtOH)10 (PCC)2(µ-PCC)2 (µ-4,4′-bipy)2(4,4′-bipy)](PCC)2 ∙3(4,4′-bipy)∙2EtOH∙H2O (5) and [Ba4(H2O)8(BuOH)6 (PCC)2(µ-PCC)6 (4,4′-bipy)6]∙3(4,4′-bipy) (6). 4,4′-Bipyridine functions either as monodentate or bidentate ligand and is present in all cases except for 2 as lattice guest. While in compounds 1 and 2 only water is present as O-donor, the alcohol coordinates in the other compounds either exclusively (3) or together with water (4–6). The pentacyanocyclopentadienide does not coordinate in 1–3, but is present as mono-, bi-, or tridentate ligand in 4–6. In all compounds, a more or less complicated interplay of hydrogen bridges and π–π stacking is observed.